The Influence of The Use of Canva-Based Video Learning Media on The Mathematical Problem-Solving Ability of Class XII Students of SMA Negeri 1 Air Joman - Dewi Astuti; Eva Margaretha Saragih; Nova Eliza Silaen (Jurnal Pendidikan Matematika (JPM), 2024)
This research aims to determine the effect of using Canva-based video learning media on the mathematical problem solving abilities of class XII students at SMA Negeri 1 Air Joman. This type of research is quasi-experimental with a two-group pretest and posttest research design. The population in this study were all students of class XII Science consisting of 3 classes. The research samples used were 2 classes (Class XII IPA-2 and XII IPA-3) with 30 students in each class. In class XII IPA-3 was an experimental class using Canva-based learning video media and in class XII-2 as a control class without using Canva-based learning video media. After the learning was completed, a posttest was obtained with an average result for the experimental class of 80.5 and the control class of 76.4. The t-test results obtained t_count (3.774)> t_table (2.001). H_a is accepted, thus there is a positive and significant influence in the use of Canva-based video learning media on the mathematical problem-solving abilities of class XII students at SMA Negeri 1 Air Joman.